2021
DOI: 10.1007/s13346-021-00977-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-responsive delivery systems for the treatment of chronic inflammatory diseases

Abstract: Graphical abstract Inflammation is the biological response of immune system to protect living organisms from injurious factors. However, excessive and uncontrolled inflammation is implicated in a variety of devastating chronic diseases including atherosclerosis, inflammatory bowel disease (IBD), and rheumatoid arthritis (RA). Improved understanding of inflammatory response has unveiled a rich assortment of anti-inflammatory therapeutics for the treatment and management of relevant chronic diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 139 publications
(106 reference statements)
0
22
0
Order By: Relevance
“…In order to deliver the anti-COVID-19 agents, either immunomodulator or not, in a selective and specific manner to the injury site, drug delivery systems can be modified to smartly respond to the specific stimuli of the inflammatory microenvironment by releasing their cargo ( Table 2 ) [ [96] , [97] , [98] , [99] ]. The inflammatory biochemical stimulus can be the low pH, the high level of reactive oxygen species (ROS), or the overexpressed inflammatory enzymes [ 95 , 100 ].…”
Section: Implications Of Inflammation In Covid-19 Therapies and Drug ...mentioning
confidence: 99%
“…In order to deliver the anti-COVID-19 agents, either immunomodulator or not, in a selective and specific manner to the injury site, drug delivery systems can be modified to smartly respond to the specific stimuli of the inflammatory microenvironment by releasing their cargo ( Table 2 ) [ [96] , [97] , [98] , [99] ]. The inflammatory biochemical stimulus can be the low pH, the high level of reactive oxygen species (ROS), or the overexpressed inflammatory enzymes [ 95 , 100 ].…”
Section: Implications Of Inflammation In Covid-19 Therapies and Drug ...mentioning
confidence: 99%
“…LPSs are produced and secreted by gram-negative bacteria (e.g., Salmonella typhimurium 53 and E. coli 54 ), and can provoke an immune response. LPSs are generally soluble as monomers but they can aggregate into fibrous and highly insoluble lipoproteins and lead to inflammation 55 . It has been reported that the concentration of LPS is increased in the acute phases of the disease compared to relapsing ones 56 .…”
Section: Metabolic and Subsystem Signature Of Each Phasementioning
confidence: 99%
“…As for biological therapeutics, their clinical applications have also been compromised due to low stability and bioavailability, high cost, primary/secondary non-responses, and the increased risk of infections or malignancies 4 , 22 , 23 . Regardless of small molecular agents and biological therapies against inflammatory diseases, their systemic exposure or non-specific biodistribution post oral or parenteral administration is a key issue responsible for their adverse drug reactions 24 , 25 , 26 . Therefore, both new drugs and creative delivery strategies are necessary to achieve more desirable treatment of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%